2020
DOI: 10.1002/fsn3.2083
|View full text |Cite
|
Sign up to set email alerts
|

CFD simulation and experimental validation of in‐container thermal processing in Fesenjan stew

Abstract: The purpose of the study was to develop and validate the CFD model for predicting temperature profile and determine the slowest heating zone (SHZ) during the thermal processing of Fesenjan stew. The temperature profile was recorded experimentally at a point where it was predicted to be the SHZ. The results showed that the SHZ was located at the geometric center of the containers, and the temperature reached 120.3 °C. The average temperatures of experiment versus predicted temperatures at the same positions, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The results revealed that the closed‐loop heating system was superior to the open‐loop heating system due to improved pasteurization efficiency resulting from a sharp increase in velocity, shorter heating time, and the ability to maintain a more stable temperature. Serami et al (2021) simulated and experimented with the thermal processing of Fesenjan stew, studying the resulting temperature profiles and location of the SHZ. The results from the mathematical model confirmed the accuracy of the proposed CFD model, which showed minimal deviation from the experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that the closed‐loop heating system was superior to the open‐loop heating system due to improved pasteurization efficiency resulting from a sharp increase in velocity, shorter heating time, and the ability to maintain a more stable temperature. Serami et al (2021) simulated and experimented with the thermal processing of Fesenjan stew, studying the resulting temperature profiles and location of the SHZ. The results from the mathematical model confirmed the accuracy of the proposed CFD model, which showed minimal deviation from the experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis and optimization of thermal processes essentially focus on the simulation of heat transfer and mass diffusion in food products by considering different thermal conditions (Feyissa, Gernaey, & Adler‐Nissen, 2013). The development of Computational Fluid Dynamic (CFD) models have been implemented in the design and prediction of the heat transfer coefficient during thermal treatment (Norton, Tiwari, & Sun, 2013; Soleymani Serami, Ramezan, & Khashehchi, 2021).…”
Section: Introductionmentioning
confidence: 99%